A retrospective study of predictive factors for effective aripiprazole augmentation of antidepressant therapy in treatment-resistant depression - Sugawara H (Dove Medical Press, 2016)
Hiroko Sugawara,1,2 Kaoru Sakamoto,1 Tsuyoto Harada,3 Satoru Shimizu,4 Jun Ishigooka1 1Department of Psychiatry, Tokyo Women’s Medical University, 2Support Center for Women Health Care Professionals and Researchers, Tokyo Women’s Medical University, Shinjuku-ku, 3Department of Psychiatry, Tokyo Women’s Medical University Medical Center East, Arakawa-ku, 4Department of Research, Medical Research Institute, Tokyo Women’s Medical University, Shinjuku-ku, Tokyo, Japan Background: Several studies have evaluated the efficacy and tolerability of aripiprazole for augmentation of antidepressant therapy for treatment-resistant depression (TRD). Here, we investigated the efficacy of aripiprazole augmentation for TRD including both major depressive disorder and bipolar disorder and the clinical predictors of treatment efficacy in a Japanese population.  Methods: Eighty-five depressed Japanese patients who underwent aripiprazole augmentation therapy after failing to respond satisfactorily to antidepressant monotherapy were included in the study. Treatment responses were evaluated based on Clinical Global Impression Improvement scores assessed 8 weeks after initiation of aripiprazole administration. We compared demographic and diagnostic variables, psychiatric medication variables, and clinical variables between remission and nonremission groups.  Results: The aripiprazole augmentation remission rate was 36.5%. Multiple logistic regression analysis indicated that aripiprazole augmentation was significantly more effective for bipolar depression than for major depressive disorder, and both absence of comorbid anxiety disorders and current episode duration >3 months were significantly associated with the efficacy of aripiprazole augmentation.  Conclusion: Polarity of depression, comorbidity of anxiety disorders, and current episode duration may predict the efficacy of aripiprazole augmentation for TRD including both major depressive disorder and bipolar disorder. Among them, comorbidity of anxiety disorders was significantly related to the efficacy for TRD including only major depressive disorder. Additional studies are needed to examine the association between the efficacy of aripiprazole augmentation and bipolarity, and these findings should be validated further in a prospective study. Keywords: TRD, aripiprazole, predictor, bipolar depression, anxiety disorder